2011
DOI: 10.1007/s10854-011-0563-y
|View full text |Cite
|
Sign up to set email alerts
|

Spectral optoelectronic features of Cu-containing arsenic sulfide (As2S3)0.95Cu0.05

Abstract: Chalcogenide amorphous thin films of the modification (As 2 S 3 ) 0.95 Cu 0.05 were prepared using a thermal evaporation technique. The optical properties of the resultant films were investigated based on the transmittance spectra in the photon energy range 1.6-2.82 eV. Thicknesses of the films under study were determined using the envelope technique based on the transmittance spectra. The optical measurements were carried out over the conditional temperature extending from 77 to 300 K. The results of the ment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The corresponding values for configuration Cu 0.25 As 2 S 3 are 9.5, 10.6, and 11.5, respectively, and the average value is 10.5. The experiments [ 7 ] show that ε 1 (0) for Cu 0.05 (As 2 S 3 ) 0.95 configuration with 1 at% Cu concentration is between 1.636 and 2.449 at different temperatures. However, the calculated average value of ε 1 (0) with 2.4 and 4.8 at%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding values for configuration Cu 0.25 As 2 S 3 are 9.5, 10.6, and 11.5, respectively, and the average value is 10.5. The experiments [ 7 ] show that ε 1 (0) for Cu 0.05 (As 2 S 3 ) 0.95 configuration with 1 at% Cu concentration is between 1.636 and 2.449 at different temperatures. However, the calculated average value of ε 1 (0) with 2.4 and 4.8 at%.…”
Section: Resultsmentioning
confidence: 99%
“…Badr et al [ 7 ] investigated the optical properties of thin films of (As 2 S 3 ) 0.95 Cu 0.05 in the photon energy range 1.6–2.82 eV and observed that Cu causes a decrease in the optical bandgap and the gap decreases with the increase in temperature. Ubale et al [ 8 ] found that the electrical resistivity, activation energy, and optical bandgap decrease with Cu doping in As 2 S 3 thin films and these thin films exhibit n‐type conductivity.…”
Section: Introductionmentioning
confidence: 99%